Euskararen zatiketa informazionalaren eredu baterantz - Isabel Gómez (Anuario del Seminario de Filología Vasca "Julio de Urquijo", 1996)
The purpose of this paper is to develop a model of informational segmentation for Basque on the basis of Asher's (1993) Segmented Discourse Representation Theory (SDRT). A new theory of the categories focus and informational theme is proposed which distinguishes between main focus and main theme. It is also shown that the means to codify these notions in Basque are mainly neutral word order and movement of constituents (to preverbal position, and to initial and final position in the sentence). Finally, we analyze (by means of formal restrictions) the interaction between informational segmentation and two types of contexts: question-answer pairs and corrections.